PENERAPAN APLIKASI E-LEARNING MADRASAH DI MA DARUL HIKMAH PEKANBARU - Maya Agustia Ningsih; Suci Dila Melani; Mitri Irianti; Muhammad Amin (STKIP Pesisir Selatan, 2022)
The Covid-19 pandemic has had a real impact in various fields of life, one of which is education. Learning activities that are carried out directly for a moment are converted into an online system that utilizes various applications that support distance learning such as the Madrasah E-learning application developed by the Ministry of Religion. MA Darul Hikmah Pekanbaru is one of the madrasas that uses Madrasah E-learning applications in the learning process. The method used in this study is a descriptive method which aims to create a systematic, factual and accurate description of the facts on the phenomena being investigated. Data collection techniques used are observation and interviews. The purpose of the research in this article is to find out how to use E-Learning Madrasas and find out the advantages and disadvantages of the E-learning application at MA Darul Hikmah. In using the E-learning application, there are main features in the madrasa E-learning application, namely online classes, teacher sharing and madrasa community forums, so that it can support the learning process at MA Darul Hikmah to be effective and systematic. Another advantage is that there are six access roles, namely madrasa operators, subject teachers, counseling guidance teachers, homeroom teachers, students and supervisors, so that all parties in the school have their respective roles in the online learning process. Weaknesses in the E-Learning Application is the internet network which is sometimes not good.